2020
DOI: 10.1039/d0ra04482b
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of biosynthesis parameters, stability and biological activities of silver nanoparticles synthesized by Cornus Officinalis extract under 365 nm UV radiation

Abstract: We present herein a systematically evaluation of the biosynthesis parameters on the green synthesis of AgNPs by utilizing Cornus officinalis extract under 365 nm UV radiation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 44 publications
(62 reference statements)
4
13
0
Order By: Relevance
“…By using the GraphPad Prism 8.0 soware package, the IC 50 values of AgNPs against these three cancer cell lines were further determined to be 13.07, 19.67 and 26.18 mg mL À1 , respectively. These values were comparable to the AgNPs synthesized using traditional medicine with anticancer effect, such as Iresine herbstii (51 mg mL À1 for Hela), 40 Sesbania grandiora (20 mg mL À1 for MCF-7), 24 Cornus officinalis (20.68 and 69.72 mg mL À1 for HCT116 and HepG2) 22 and Sea buckthorn (8.77, 4.61, 14.59, 16.05 and 27.98 mg mL À1 for HCT116, SW620, HepG2, MCF-7 and HeLa), 21 indicating that the AgNPs synthesized using RBM extract could be a potential candidate for anticancer drugs.…”
Section: Anticancer Activities Of Biosynthesized Agnpssupporting
confidence: 64%
See 1 more Smart Citation
“…By using the GraphPad Prism 8.0 soware package, the IC 50 values of AgNPs against these three cancer cell lines were further determined to be 13.07, 19.67 and 26.18 mg mL À1 , respectively. These values were comparable to the AgNPs synthesized using traditional medicine with anticancer effect, such as Iresine herbstii (51 mg mL À1 for Hela), 40 Sesbania grandiora (20 mg mL À1 for MCF-7), 24 Cornus officinalis (20.68 and 69.72 mg mL À1 for HCT116 and HepG2) 22 and Sea buckthorn (8.77, 4.61, 14.59, 16.05 and 27.98 mg mL À1 for HCT116, SW620, HepG2, MCF-7 and HeLa), 21 indicating that the AgNPs synthesized using RBM extract could be a potential candidate for anticancer drugs.…”
Section: Anticancer Activities Of Biosynthesized Agnpssupporting
confidence: 64%
“…To date, several plant including Coconut inflorescence sap, 13 Citrus reticulata peels, 15 grape seed, 16 Arbutus unedo , 17 Nelumbo nucifera , 18,19 Fumaria parviflora , 20 and Coffea arabica 10 have been employed for biosynthesizing AgNPs with different physicochemical and biological properties. Especially, since it is rich of bioactive ingredients, traditional Chinese herbal medicines (CHMs) like Sea buckthorn , 21 Cornus officinalis , 22 Iresine herbstii , 23 Sesbania grandiflora 24 and Alpinia katsumadai 25 have also attracted enormous attentions for biosynthesizing medicinal AgNPs.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the obtained results are compatible with those recorded by He et al [81], who reported that the IC 50 of the HepG2 cell line treated with Ag-NPs synthesized by aqueous fruit extract of Chinese herbal Cornus officinalis for 48 h was 21.46 µg mL −1 . On the other hand, data recorded by Wang et al [82] showed that the IC 50 of Ag-NPs fabricated by extract of Cornus officinalis under UV-radiation was 69.72 mg mL −1 for the HepG2 cancerous cell line. There is variation between the IC 50 values recorded by He et al [81] and Wang et al [82], although the Ag-NPs synthesized using the same aqueous plant extract could be attributed to the bioactive metabolites involved in the plant extract used for reducing and capping Ag-NPs, particles sizes, or biosynthesis environmental conditions [82].…”
Section: In Vitro Cytotoxicitymentioning
confidence: 93%
“…The IC 50 values of AgNPs against HCT116, HepG2, and HeLa cancer cell lines were determined by fitting the curve of the cell viability using the GraphPad Prism 8.0 software package, and the values were 9.0, 14.5, and 31.5 μg·mL –1 , respectively. The AgNPs synthesized by the Mentha pulegium extract herein displayed a higher anticancer activity than the AgNPs synthesized by Hadi Faranak using Iranian Mentha pulegium (∼100 μg·mL –1 for Hela and MCF-7), 46 and other traditional medicines with an anticancer effect, such as Iresine herbstii ( 60 ) (51 μg·mL –1 for Hela) and Cornus officinalis ( 31 ) (20.68 and 69.72 μg·mL –1 for HCT116 and HepG2, respectively). Additionally, these values were also comparable to those of Sea buckthorn ( 30 ) (8.77, 14.59, and 27.98 μg·mL –1 for HCT116, HepG2, and HeLa, respectively), indicating that the AgNPs biosynthesized using Mentha pulegium extract could be acted as candidate for anticancer drugs.…”
Section: Resultsmentioning
confidence: 89%
“… 22 , 27 Thus, traditional Chinese medicines have attracted considerable attention from analysts due to medicinal components in them. 28 34 To date, numerous Chinese herbal medicines such as Sea buckthorn , 30 , 35 Zizyphus mauritiana , 36 Nelumbo nucifera , 37 , 38 and Cornus officinalis ( 31 , 33 , 39 , 40 ) have been employed for the synthesis of bioactive AgNPs.…”
Section: Introductionmentioning
confidence: 99%